What are benefit-sharing mechanisms? - Bievre, B. de; Luis, A.; Miguel, S.; Thomas, S.; Dora, A. (CONDESAN, 2014)
An introductory video to Benefit-Sharing Machanisms. Discover how Benefit-Sharing Mechanisms (BSMs) work to redistribute the costs and benefits of a healthy watershed equitably amongst everyone.